Analyzing the effect of severe weather on farmers' fertilizer usage and input investment amidst decreasing productivity in single-season agroecosystems - Atinga, David; Awuni, Joseph Agebase; Sakurai, Takeshi (Frontiers in Environmental Economics, 2024)
Introduction In Ghana and comparable developing countries, advancing farm investments and adopting innovative rice farming techniques encounters obstacles because of climate change. Smallholder farming households, affected by climate events, confront substantial risks that affect both agricultural returns and investment decisions. Methods This research evaluates the enduring impact of fluctuating weather patterns in a single-cropping agroecological region on rice yields, examining the consequent influence on the utilization of inorganic fertilizers and agricultural input investment among rain-fed households, investigating disparities, reasons, and underlying mechanisms. The research used panel data from 60 communities, employing regression analysis and probability models. It integrated monthly cropping season weather data across the study zone's grid cells for community-level time series analysis. Results and discussion The results suggest that while weather shocks have a minimal impact on farmers abandoning inorganic fertilizers altogether, they do significantly decrease the overall amount of fertilizer used, agricultural investments, and rice crop yields. Floods and severe shocks exert a more pronounced influence compared to droughts and moderate shocks. Off-farm employment aids households in recovering from these shocks and maintaining agricultural investments. Climate shocks impact agricultural investment by reducing farm household income via altering crop yield and revenue. Consequently, this disrupts their ability to save, resulting in financial constraints. Encouraging and sustaining farm investments in vulnerable agrosystems involves diversifying income sources through combined crop and livestock farming, supplemented by off-farm activities. This strategy is fortified by climate-resilient farming practices, including resilient crop varieties supported by irrigation, weather insurance, and risk-oriented credit.